Budrus - Bacha, Julia (Palestine; Israel; USA; Just Vision Films, 2009)
The documentary follows a Palestinian leader who unites Fatah, Hamas and Israelis in an unarmed movement to save his village from destruction. Success eludes them until his 15-year-old daughter jumps into the fray.
Verzio Film Festival Submission
Keywords: Documentary films